2019
DOI: 10.1590/0103-6564e20180176
|View full text |Cite
|
Sign up to set email alerts
|

Activación emocional en sujetos humanos: procedimientos para la inducción experimental de estrés

Abstract: Resumen El estudio de los efectos del estrés sobre la cognición y el comportamiento es un área de especial interés y desarrollo científico, tanto para la Psicología como para las Neurociencias. La inducción de estrés constituye un elemento fundamental en estos estudios, pues permite la manipulación de esta forma de activación emocional, como variable independiente, para observar su efecto sobre la conducta; no obstante, esta inducción debe ser suficiente para generar incrementos significativos en los niveles d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Relatives may join social movements intending to denounce the traumatizing actions inflicted on their loved ones. Their narrated testimonies may favor the representation of their trauma, fostering a symbolic construction that moves a subject away from traumatic paralysis (Ferreira & Caniato, 2019). Collective acts are fundamental.…”
Section: The Collective-symbolic: An Attempt At Mourning In Families ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Relatives may join social movements intending to denounce the traumatizing actions inflicted on their loved ones. Their narrated testimonies may favor the representation of their trauma, fostering a symbolic construction that moves a subject away from traumatic paralysis (Ferreira & Caniato, 2019). Collective acts are fundamental.…”
Section: The Collective-symbolic: An Attempt At Mourning In Families ...mentioning
confidence: 99%
“…They found that spouses and parents of missing persons appeared the most affected and that the number of traumatic events that family members had been exposed to was significantly associated with increased levels of psychopathology (Lenferink et al, 2019). Ferreira and Caniato (2019) addressed mourning vis-à-vis persons who disappeared for political reasons during Brazil’s military dictatorship. They discovered that melancholy paralyzed subjects into a mortifying state in such types of loss.…”
Section: The Collective-symbolic: An Attempt At Mourning In Families ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of experiments on humans requires the creation of non-invasive procedures that guarantee limited effects, do not persist in the long term, and generate moderate levels of stress, sufficient to observe their effects without generating harm to the study participants. As mentioned by Ferreira 16 “stress induction procedures must include elements of novelty, unpredictability, loss of control, representing a potential threat or loss, and, in some cases, social evaluation”. Only three publications have described the characterization of VOCs emitted during psychological stress in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both the SCWT and emotional content in the tasks were shown to be effective at inducing stress in a controlled laboratory setting 43 . In terms of methodology, some of the studies used some form of stress-inducing material 22 , 23 , 33 , 38 , 41 , 42 , although none of them specifically investigated the potential mediating or moderating role of the activation of the SRS during the task.…”
Section: Introductionmentioning
confidence: 99%